Natural Frequency of Liquefaction Potential Based on Soil Investigation and Microtremor Observation Results - Putra, Rusnardi Rahmat; Kiyono, Junji; Zhang, Zhenghu; Vanapalli, Sai; Agung, M. Darma (Civil Engineering Journal, 2025)
This study aims to identify the natural frequency threshold for liquefaction potential by comparing four assessment methods at 54 identical sites in Padang, Indonesia. Methods include: (1) safety factor calculations from soil investigation results (CPT and SPT) applying the 2009 Padang earthquake's peak ground acceleration as input for cycling stress ratio; (2) natural frequency measurements at the surface using microtremor single observations; (3) liquefaction potential assessment through vulnerability index; and (4) analysis of historical liquefaction events from the September 30, 2009 Padang earthquake documented in two previous research papers. The analysis focused on soil depths ranging from 1-4 m. Findings reveal that sites with natural frequencies exceeding 0.40 Hertz remain safe from liquefaction, while sites with frequencies between 0.20-0.39 Hertz demonstrate significant liquefaction potential. This research contributes to the field by establishing a clear correlation between measurable natural frequency thresholds and liquefaction risk, providing engineers and urban planners with a more accessible parameter for preliminary risk assessment. Integrating multiple assessment methods at identical sites enhances the reliability of the identified frequency thresholds, offering a more comprehensive approach to liquefaction hazard mitigation in earthquake-prone regions.